ANALISIS SISTEM KERJA AUTOMATIC TRANSFER SWITCH (ATS) PADA PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) TERHADAP NILAI TEGANGAN BATERAI - Sitohang, Theresia Bornito; Satria, Beni; Tarigan, Amani Darma (Power Elektronik : Jurnal Orang Elektro, 2024)
The application of protection systems and Automatic Transfer Switch (ATS) is important to ensure the safe operation of the power system, especially the Solar Power Plant (PLTS). So in this study the authors analysed and evaluated the impact of the application of the Automatic Transfer Switch (ATS) system on Solar Power Plants (PLTS). By using a protection system for battery voltage, overvoltage and undervoltage protection and load current limitation, to protect electrical equipment connected to the Solar Electric System (PLTS). Automatic Transfer Switch (ATS) serves as a transfer medium to the PLN power source if it is detected that the availability of electrical power in the PLTS system is insufficient. The test results show that the protection system applied to the battery can protect the battery's performance in supplying electricity to the electrical load, where if it is indicated that the battery voltage has dropped to the minimum limit set (10 volts), the protection system will automatically cut off the electricity supply from the battery and will be transferred to the electricity supply from PLN through the ATS. If the battery voltage is detected to reach 12 volts, the Automatic Transfer Switch (ATS) will automatically connect the electricity supply to the PLTS system. The protection system will also protect electrical equipment against Over Voltage, 231 Volts and Under Voltage 198 Volts. If this happens, the electricity supply to the load will automatically be cut off.